2012
DOI: 10.1007/s12262-012-0543-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Supplementing Preoperative Intravenous Omega 3 Fatty Acids in Fish Oil on Immunomodulation in Elderly Patients Undergoing Hip Surgery

Abstract: The aim of this study was to evaluate the immu-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The level of evidence for an anti-inflammatory effect of n -3 PUFA supplementation in older individuals is perhaps more solid, as shown in Table 2 . In two RCTs carried out on older individuals undergoing hip surgery [ 96 ] or admitted to ICU with critical illness [ 97 ], the intravenous administration of fish oil-based lipid emulsions for eight days was effective to increase the circulating levels of the anti-inflammatory cytokine IL-10. A decrease in serum levels of IL-8, TNF-α and IL-6 levels was also observed [ 96 , 97 ].…”
Section: N -3 Polyunsaturated Fatty Acids and Imentioning
confidence: 99%
See 1 more Smart Citation
“…The level of evidence for an anti-inflammatory effect of n -3 PUFA supplementation in older individuals is perhaps more solid, as shown in Table 2 . In two RCTs carried out on older individuals undergoing hip surgery [ 96 ] or admitted to ICU with critical illness [ 97 ], the intravenous administration of fish oil-based lipid emulsions for eight days was effective to increase the circulating levels of the anti-inflammatory cytokine IL-10. A decrease in serum levels of IL-8, TNF-α and IL-6 levels was also observed [ 96 , 97 ].…”
Section: N -3 Polyunsaturated Fatty Acids and Imentioning
confidence: 99%
“…In two RCTs carried out on older individuals undergoing hip surgery [ 96 ] or admitted to ICU with critical illness [ 97 ], the intravenous administration of fish oil-based lipid emulsions for eight days was effective to increase the circulating levels of the anti-inflammatory cytokine IL-10. A decrease in serum levels of IL-8, TNF-α and IL-6 levels was also observed [ 96 , 97 ]. Interestingly, Berger et al , in a RCT enrolling both adult and geriatric patients undergoing cardiopulmonary bypass surgery, showed that n -3 PUFA decreased the perioperative inflammation [ 98 ].…”
Section: N -3 Polyunsaturated Fatty Acids and Imentioning
confidence: 99%
“…Moreover, their synthesis is extremely limited in most mammals (less than 5% of the precursors are converted) [16]. Increasing data in animal models as well as in humans suggest that dietary PUFA exert immunomodulatory effects [17][18][19][20]. Indeed, n-3 long chain PUFAs form the basis of lipid derivatives (neuroprotectins and resolvins) with anti-inflammatory properties [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%